Development of Virtual Laboratory Based on Mobile Learning in Bromo Tengger Semeru National Park Area - Bashith, Abdul; Amin, Saiful; Kurniawan, Muchammad Akbar; Dewi, Sari (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Mobile learning-based digital field laboratories have not been widely developed in the learning process. Currently, the development of mobile learning-based virtual laboratories needs to be done to assist learning both online and offline. This study aims to explain the process of developing mobile learning-based virtual laboratories and also discuss the effect of using mobile learning-based virtual laboratories on student learning outcomes. This study uses the Borg & Gall Research and Development (R&D) model. The suitability of the product has been tested by expert validators on media and learning materials. Product effectiveness data has been tested on students using normality tests, homogeneity tests and independent sample t-tests. The increase in Gain score in the experimental group using mobile learning-based virtual laboratories was 39.04 (from 46.22 to 85.26), while the control group without a virtual laboratory increased by 25.70 (from 42.37 to 68.07). The results of the study indicate that 1) mobile learning-based virtual laboratories are feasible to use in learning with a very effective category and 2) the use of mobile learning-based virtual laboratories is effective in improving student learning outcomes in the topic of Economic Behavior of the Tengger Mountain Slope Community. This research has a positive impact on the development of knowledge of social studies education students in utilizing virtual laboratories based on mobile learning. Suggestions for further research are that the results of the development of mobile learning-based learning media products should be distributed through the app market